Study about Parenting Styles and Academic Achievement: A Theoretical Perspectives - Seng, Ngu Leh; Hanafi, Zahyah; Taslikhan, Muhajir (Research Aspects in Arts and Social Studies Vol. 9, 2023)
The present study highlights the most parents are practicing authoritative parenting style compared to other styles. A parenting style is a method or strategy used in the process of raising children. This parenting style, which is a psychological construct, represents typical parental educational methods. Type of parenting styles were found to be influences their children’s academic achievement. This study involved 406 of form 5 students as respondents. The quantitative approach-using questionnaires used meet the objectives of this study. Results of this study found that parenting styles practiced by parents according to the students' perception is authoritative style followed by style authoritarian style, permissive, and finally neglectful style. Research method can also include qualitative component, i.e. interviews in order to get a more in depth about why parents practice different parenting styles.